Different percentages of basil seeds (Ocimum basilicium L.) as hydrocolloid in batter coating system: effect on the physicochemical and sensory properties of breaded fish fillets - Asmak Abdul-Zubir; Norhidayah Suleiman; Noor Liyana Yusof; Ishamri Ismail; Mohammad Rashedi Ismail-Fitry (Penerbit Universiti Kebangsaan Malaysia, 2022)
Basil seed (Ocimum basilicium L.) has the potential to improve the characteristics of food products when added to the batter for coating but the amount could result in different qualities. This study investigates the physicochemical and sensory properties of tilapia fish fillets coated with batter added with different percentages of basil seeds (0%, 3%, 6% & 9%). The viscosity, coating adhesion, cooking yield, frying loss, moisture and fat contents, colour, texture and sensory properties were analyzed. As the basil seeds percentages added increased, the viscosity was improved and strongly correlated with the coating adhesion, cooking yield, frying loss and moisture content. The hardness, chewiness and fracturability of the fish fillet were also improved. The treated samples were darker and redder, which contributed to the golden colour. Panellists rated the crispness and overall acceptability of the treated samples higher than the control (0% of basil seed), while other parameters such as colour, appearance, fishy smell level, taste and juiciness were not different between the control and the treated samples. In conclusion, the quality of the coated fish fillet with added 3% of basil seed to the batter was not much different compared to the control (0%), while, the 9% had negatively influenced the oil adsorption and sensory characteristics of the samples. Therefore, 6% is suggested as the most suitable percentage to be used in the batter.